Invisible cultures of urban poverty in Lima: Towards a decolonial theory from global financial capitalism - Ríos Burga, Jaime (2018)
The article presents some aspects of reflection from the decolonial theory as situations of typical cases about new invisible cultures of urban poverty in Metropolitan Lima from the framework of the impact of financial capitalism and its new forms of coloniality.